2022
DOI: 10.3390/antiox11020344
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Supplementation to Serum-Free Maturation Medium Improves In Vitro Bovine Embryo Development and Quality and Modulates Embryonic Transcriptomic Profile

Abstract: Bovine embryos are typically cultured at reduced oxygen tension to lower the impact of oxidative stress on embryo development. However, oocyte in vitro maturation (IVM) is performed at atmospheric oxygen tension since low oxygen during maturation has a negative impact on oocyte developmental competence. Lycopene, a carotenoid, acts as a powerful antioxidant and may protect the oocyte against oxidative stress during maturation at atmospheric oxygen conditions. Here, we assessed the effect of adding 0.2 μM lycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 60 publications
3
14
0
2
Order By: Relevance
“…This finding suggests a role for lycopene in preserving the structural integrity of polyunsaturated fatty acids within oocytes. Consistent with our observations, a better distribution of lipid droplets has been observed in bovine oocytes after lycopene supplementation [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding suggests a role for lycopene in preserving the structural integrity of polyunsaturated fatty acids within oocytes. Consistent with our observations, a better distribution of lipid droplets has been observed in bovine oocytes after lycopene supplementation [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…This may support another study in porcine oocytes that showed a decrease in H 2 O 2 levels, and an increase in GSH concentrations, as well as CAT and SOD expression levels after supplementation of 2.5 μM astaxanthin, a ketocarotenoid with structural similarities to lycopene, during their in vitro aging for 42–44 h [ 57 ]. In addition, in bovine oocytes, lycopene supplementation to the IVM medium led to a significant reduction in ROS levels [ 37 ]. In aged porcine and mouse oocytes, reduced ROS levels have also been reported after melatonin supplementation during their in vitro aging at concentrations of 1 mM and 2 mM, respectively [ 41 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a culture medium with lesser ROS, embryos will develop and thrive. Antioxidants act via scavenging ROS, and lycopene is very efficient in doing so as has been shown in earlier studies by our group (Residiwati et al, 2021; Sidi et al, 2022). In vitro production of embryos with higher TCN is essential for a subsequent successful pregnancy.…”
Section: Discussionsupporting
confidence: 77%
“…Lycopene is a natural carotenoid antioxidant (Bramley, 2000) with potent quench singlet oxygen capacity (Imran et al, 2020). Recent studies showed that lycopene supplementation in the maturation medium improves the development and quality of bovine blastocysts under serum‐free conditions (Residiwati et al, 2021; Sidi et al, 2022). We hypothesize that the antioxidant capacity of lycopene supplementation combined or not with S results in a more efficient reactive oxygen species depletion in the culture medium.…”
Section: Introductionmentioning
confidence: 99%